Analisis Kinerja Lingkungan Dan Produktivitas Dengan Menggunakan Konsep Green And Lean Productivity - Muhammad Hanifuddin Hakim; Ahmad Mubin (Department Industrial Engineering, University of Muhammadiyah Malang, 2016)
Regional Water Company (PDAM) Lamongan is a local company with main activity is to serve and provide clean water to communities through a system of pipes. Constraint occurs is in the process of drinking water treatment and wastewater sludge yield potential as a source of environmental pollution. Another problem is still limited because of PDAM services in 2013 is only capable of serving 4.7% of the total number of households (BPS population census of 2010). Taps need to increase the amount of water production in order to serve the wider community Lamongan. The concept of green productivity (GP) can be used in the search for solutions to increase productivity and protect the environment. The study begins by identifying the root cause of a lot of liquid waste and a low amount of water production, setting objectives and targets, choosing the resources and information available to arrange alternative green productivity. There are two alternatives, the selected alternative in this study are alternative 2 merge maximizing the raw water intake (pipe repair, purchase and installation of the intake screen 2 pump intake of government), Repair IPA II, and the use of wastewater that is the use of waste as material raw returned by first applying multilevel aeration technology to reduce levels of COD and BOD5 in wastewater. The productivity of the company in the first year after implementation of the selected alternative to 123%, an increase of 14% compared to the year 2013 and the total value of the EPI index to 18.35 or increased 42.65, which means it meets effluent standards wastewater East Java Governor Regulation No. 72 of 2013. In addition the production of water PDAM also increased 69.8% over the previous year.